Dopamine-receptor 2 gene-methylation and gambling behavior in relation to impulsivity. (30th May 2016) - Hillemacher, Thomas; Frieling, Helge; Buchholz, Vanessa; Hussein, Rim; Bleich, Stefan; Meyer, Christian; John, Ulrich; Bischof, Anja; Rumpf, Hans-Jürgen
Highlights: DRD2 methylation is associated with gambling in subjects with high impulsivity. In subjects with low Impulsivity other neurobiological pathways may be involved. These findings may be important for studies on impulsivity in pathologic gambling.